(Des)igualdad y anarquismo. Derecha e izquierda en el ideario anarquista - Garaventa, Carlos A. (2011)
Within anarchism, we may find so many different strains that providing\na univocal definition of this philosophy ?that we might well consider a lifestyle? is\ndefinitely unfeasible. However, we may point out a feature that is shared by all of\nthem: the promotion of a stateless society. Further, in a ?pure? anarchism, French\nRevolution?s three foundating ideals are always present, but with a different dynamics:\ninstead of considering them in isolation, the trinomial must be viewed as a whole:\nthis will give place to the liberty, equality and fraternity virtuous triangle. Yet, not all anarchists defend this triangle in its entirety: some authors, for instance, set aside\nequality. According to Norberto Bobbio?s classification between political left and right,\nanarchists enroling any of such wings may be differentiated taking into account their\nposition as to whether society must be egalitarian or not. In that way, those that defend\nequality and therefore, the virtuous triangle, are left-wing anarchists; in turn, rightwing\nanarchists promote a stateless society, regardless of its being egalitarian or not